Recovery of Aluminum from Aluminum Coated Plastic Waste using Pyrolysis Process - Chairul Irawan; Rinny Jelita; Iryanti Fatyasari Nata (Dept. of Chemical Engineering, Diponegoro University, 2018)
This study aims to separate aluminum metal in aluminum coated plastic waste so that it is known the obtained aluminum characteristics, to study the effects of temperature on the yield of solids and aluminum, and to get the kinetic parameters that describe the effects of temperature on pyrolysis process rate. Plastic waste was cleaned, dried, cut, and weighed as much as 100 grams. Pyrolysis lasted in room temperature in 2 hours after the pyrolysis temperature was reached, i.e. 450oC. The formed smoke was condensed and weighed every 10 minutes from the first droplet until the pyrolysis time was completed. The remaining solids in the reactor were taken after the pyrolysis was completed and reactor temperature reached room temperature. The aluminum mixture was subsequently melted, molded and cooled. Experiments were repeated in various pyrolysis temperature variations (500°C, 550°C, 600°C and 650°C). The results show that the increase of pyrolysis temperature will decrease the yield of solids, while the aluminum yield remains. The obtained aluminum metal is 5.3% against the initial plastic mass in purity of 95.80%. The kinetic model representing plastic pyrolysis process is a single reaction model with the value of kinetic parameters of pre-exponential factor (A) 18.2689 min-1 and the activation energy value (E) 40.2310 kJ/mole. Keywords: aluminum, pyrolysis, plastic wastes, temperature, kinetic parameter